2022
DOI: 10.1021/acschemneuro.2c00099
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid-Derived Carbon Quantum Dots Attenuate Paraquat-Induced Neuronal Compromise In Vitro and In Vivo

Abstract: The potent environmental herbicide and weedicide paraquat is linked to neuromotor defects and Parkinson's disease (PD). We have evaluated the neuroprotective role of citric acidsourced carbon quantum dots (Cit-CQDs) on paraquat-insulted human neuroblastoma-derived SH-SY5Y cell lines and on a paraquat-exposed nematode (Caenorhabditis elegans). Our data reveal that Cit-CQDs are able to scavenge free radicals in test tube assays and mitigate paraquat-elevated reactive oxygen species (ROS) levels in SH-SY5Y cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The presence of two absorption peaks at 275 and 340 nm for R-CDs indicated that rutin was successfully loaded onto CDs (Figure D). The FTIR spectra of CA, PLL, rutin, and R-CDs revealed 3000 cm –1 absorption of the O–H stretching vibration of CA and PLL, 1750 cm –1 for CO stretching for CA and PLL, and 1250 cm –1 attributed to the C–N stretching vibration of the amine group of PLL. The absorption peaks of rutin at 2800 and 1600 cm –1 represented the C–H stretching vibration and skeletal vibration of the benzene ring, respectively. , The absorption peak of the R-CDs spectrum at 1100 cm –1 was indicative of a conjugation effect following reaction of CA with PLL resulting in the disappearance of the carbonyl group and the shift of the amine group toward the lower wavenumber. The absorption peak of R-CDs at 2800 cm –1 indicated the presence of rutin that demonstrated its successful loading onto the CDs (Figure E).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The presence of two absorption peaks at 275 and 340 nm for R-CDs indicated that rutin was successfully loaded onto CDs (Figure D). The FTIR spectra of CA, PLL, rutin, and R-CDs revealed 3000 cm –1 absorption of the O–H stretching vibration of CA and PLL, 1750 cm –1 for CO stretching for CA and PLL, and 1250 cm –1 attributed to the C–N stretching vibration of the amine group of PLL. The absorption peaks of rutin at 2800 and 1600 cm –1 represented the C–H stretching vibration and skeletal vibration of the benzene ring, respectively. , The absorption peak of the R-CDs spectrum at 1100 cm –1 was indicative of a conjugation effect following reaction of CA with PLL resulting in the disappearance of the carbonyl group and the shift of the amine group toward the lower wavenumber. The absorption peak of R-CDs at 2800 cm –1 indicated the presence of rutin that demonstrated its successful loading onto the CDs (Figure E).…”
Section: Results and Discussionmentioning
confidence: 99%
“…CQDs are carbon nanomaterials that are typically between 1 and 10 nm in diameter and composed of tens or hundreds of carbon atoms. They possess excellent physical and chemical properties, as well as unique optical properties [23,24]. CQDs exhibit strong electron transfer properties and, when combined with some catalytic materials, can take full advantage of visible and UV light to generate more efficient photogenerated electron-hole pairs [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The SHSY-5Y cell-line is a neuroblastoma-derived cell line that frequently is used as a neuronal mimic for assessing cellular homeostasis (or induction of dyshomeostasis) as a function of environmental neurotoxicants including pesticides such as PQ and rotenone . It serves as a vehicle for investigating outcomes associated with the trajectory to Parkinson’s disease including apoptosis/necrosis, elevated levels of free radicals, aggregation of heat shock proteins, increased protein ubiquitination levels, and the accumulation of Lewy bodies …”
Section: Introductionmentioning
confidence: 99%
“…For example, the pesticide PQ has been used in C. elegans to evaluate oxidative damage to neurons at the molecular, cellular, and behavioral level. , Similarly, the effect of rotenone and paraquat in the pathogenesis of Parkinson’s disease has been studied in nematodes through an analysis of its effects on mitochondria-associated membrane proteins, leading to mitochondrial damage and oxidative stress …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation